Production Economics The Basic Theory of Production Optimisation - Rasmussen, Svend (Springer Berlin Heidelberg Imprint: Springer, 2011)
This book covers the basic theory of how, what and when firms should produce to maximise profits. Based on the neoclassical theory of the firm presented in most general microeconomic textbooks, it extends the general treatment and focuses on the application of the theory to specific problems that the firm faces when making production decisions to maximise profits. Increasing level of government regulation and the use of specialised and often very expensive equipment in modern production motivates the following focus areas: 1) How to optimise production under restrictions., 2) Treatment of fixed inputs and the process of input fixation, 3) Optimisation of production over time, 4) Linear and Mixed Integer Programming as tools for optimisation in practice.